Shelf Life of Tilapia (Oreochromis niloticus) Dumplings with addition of Bagasse Liquid Smoke during Storage at Chilling Temperature (±5°C) - Eka Handayani; Fronthea Swastawati; Laras Rianingsih (Universitas Gadjah Mada, 2019)
Tilapia (Oreochromis niloticus) can be used to process fish dumplings. Tilapia dumplings are susceptible to microbiological quality deterioration so that the shelf life is low. The liquid smoke of bagasse contains phenol, acid, and carbonyl that can be used as natural preservatives to extend the shelf life of fish dumplings. The aim of this study was to determine the effect of adding bagasse liquid smoke to the quality and shelf life of tilapia dumplings by treating the concentration of liquid smoke stored in chilling temperatures (±5°C). The material used tilapia and bagasse liquid smoke. The experimental method used split-plot in time 2 factors, differences concentration of liquid smoke (0% and 2.5%) and storage time (0, 5, 10, 15, 20 days) with 3 repetitions. The testing parameters of fish dumplings are a sensory test, total phenol, TPC, TVBN, and pH. Non-parametric data were analyzed using Kruskal-Wallis and Mann-Whitney for further test. Parametric data were analyzed using ANOVA and BNJ for further test. The result shows that tilapia dumplings without the addition of liquid smoke rejected on the 10th day with a sensory value 5.63±0.47; total phenol 102.04±0.00; TPC 5.2×104±0.01CFU/g; and pH 7.42±0.08 while according TVBN value rejected on the 5th day with 15.13±0.64 mg/100g. Tilapia dumplings with addition of 2,5% liquid smoke rejected on the 15th day with an sensory value 5.87±0.45; total phenol 116.85±0.01; TPC 5.4×104±0.01CFU/g; TVBN 18.82±0.84 mg/100g and pH 7.33±0.10. Bagasse liquid smoke can increase the shelf life of tilapia dumplings up to 10 days during chilling storage.